Induced Earthquake Source Parameters, Attenuation, and Site Effects From Waveform Envelopes in the Fennoscandian Shield - Eulenfeld, Tom; Hillers, Gregor; Vuorinen, Tommi A. T.; Wegler, Ulrich (Journal of Geophysical Research: Solid Earth, 2023)
Peer reviewed